ANALISIS EFISIENSI USAHA TANI SEMANGKA DI KABUPATEN SRAGEN - Sundari, Mei Tri (Universitas Sebelas Maret, 2008)
The objective of this research is to know the revenue, cost and profit in watermellon farm. It wants to know the efficiency of watermelon farm in Sragen Regency. The method used in this research was analytical descriptive with survey in implementation. The location was selected purposively and it was Desa Pungsari, Kecamatan Plupuh, Kabupaten Sragen. Snowball sampling method is used to choose the sample. The data used in this research was primary data of cultivating season of 2006, which was the newest available data. By using R/C ratio we find that the value is 2,75 per ha. This value shows us that watermelon farm in Sragen had efficien because the value more than one. The average revenue of the farmer was 76.217.500 per ha and the cost was Rp 27.711.550 per ha.